1. The problem statement, all variables and given/known data Integrate: ((e^arccos(x))(dx))/(sqrt(1-x^2)) Image of the question is attached. 2. Relevant equations 3. The attempt at a solution I think i took the right first step for substitution: u=arccos(x); cos(u)=x; (du)(-sin(u))=dx Substituting u into the equation: ((e^u)(-sin(u))(du))/(sqrt(1-(cos(u))^2)) This is where I'm stuck. I tried all of the following second substitutions, but they either took me in circles or didn't replace all the u variables, or took me back to square one: v=cos(u) v=e^u v=1-(cos(u))^2 I am doing this for a Calculus project using the Maple 11 program. It seems to be able to integrate the problem just fine, but I can't figure it out. A .bmp image is attached if you are unsure of what I have typed for the question.